2012
DOI: 10.5009/gnl.2012.6.4.417
|View full text |Cite
|
Sign up to set email alerts
|

Role of Janus Kinase/Signal Transducers and Activators of Transcription in the Pathogenesis of Pancreatitis and Pancreatic Cancer

Abstract: In the pathogenesis of pancreatitis, oxidative stress is involved in the activation of the Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway and cytokine expression. High serum levels of cholecystokinin (CCK) have been reported in patients with acute pancreatitis, and treatment with cerulein, a CCK analogue, induces acute pancreatitis in a rodent model. Recent studies have shown that cerulein-activated nicotinamide adenine dinucleotide phosphate oxidase elicits reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Previous studies have demonstrated in several models of acute pancreatitis, including CCK-induced, that there is activation of several important transcriptional factors such as NF-B (25,27,30,56,62), STAT-3 (9,33,62,89), and AP-1 (26,33,62). Our results support the conclusion that, in pancreatic acinar cells, the CCK-induced activation of NF-B, STAT-3, and AP-1 is Src-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated in several models of acute pancreatitis, including CCK-induced, that there is activation of several important transcriptional factors such as NF-B (25,27,30,56,62), STAT-3 (9,33,62,89), and AP-1 (26,33,62). Our results support the conclusion that, in pancreatic acinar cells, the CCK-induced activation of NF-B, STAT-3, and AP-1 is Src-dependent.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have also found that immune cells have less responsiveness to type III IFNs [12,32]. However, IL-28A did activate keratinocytes, melanocytes and hepatocytes to induce phosphorylation of STAT1, which is critical for production of inflammatory cytokines such as TNF-a, IL-1b and IL-6 [7,33]. These cytokines may in turn affect T cell polarization.…”
Section: Discussionmentioning
confidence: 85%
“…The Janus kinase 2 (JAK2)/STAT3 pathway is well known to be involved in the immune response of numerous cytokines, including TNF-α and IL-6 (6). In addition, evidence derived from numerous clinical and experimental studies suggests the involvement of the JAK2/STAT3 pathway in pancreatitis (7)(8)(9) or renal diseases (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%